Adhesion and biofilm formation on polystyrene by drinking water-isolated bacteria - Simões, Lúcia C. (2010)
This study was performed in order to characterize the relationship between adhesion and biofilm formation abilities of drinking water-isolated bacteria (Acinetobacter calcoaceticus, Burkholderia cepacia, Methylobacterium sp., Mycobacterium mucogenicum, Sphingomonas capsulata and Staphylococcus sp.). Adhesion was assessed by two distinct methods: thermodynamic prediction of adhesion potential by quantifying hydrophobicity and the free energy of adhesion; and by microtiter plate assays. Biofilms were developed in microtiter plates for 24, 48 and 72 h. Polystyrene (PS) was used as adhesion substratum. The tested bacteria had negative surface charge and were hydrophilic. PS had negative surface charge and was hydrophobic. The free energy of adhesion between the bacteria and PS was[0 mJ/m2 (thermodynamic unfavorable adhesion). The thermodynamic approach was inappropriate for modelling adhesion of the tested drinking water bacteria, underestimating adhesion to PS. Only three (B. cepacia, Sph. capsulata and Staphylococcus sp.) of the six bacteria were non-adherent to PS. A. calcoaceticus, Methylobacterium sp. and M. mucogenicum were weakly adherent. This adhesion ability was correlated with the biofilm formation ability when comparing with the results of 24 h aged biofilms. Methylobacterium sp. and M. mucogenicum formed large biofilm amounts, regardless the biofilm age. Given time, all the bacteria formed biofilms; even those non-adherents produced large amounts of matured (72 h aged) biofilms. The overall results indicate that initial adhesion did not predict the ability of the tested drinking water-isolated bacteria to form a mature biofilm, suggesting that other events such as phenotypic and genetic switching during biofilm development and the production of extracellular polymeric substances (EPS), may play a significant role on biofilm formation and differentiation. This understanding of the relationship between adhesion and biofilm formation is important for the development of control strategies efficient in the early stages of biofilm development.